A residential gateway architecture based on Cloud computing - Zhiqiang Wei; Jing Li; Yongquan Yang; Dongning Jia (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
The residential gateway plays a significant role in a Smart Home, which connects the home network and the public network. There are various gateway architectures for the Smart Home. With the development of Cloud Computing, it is hoped that Smart Home can merge into the Clouds to provide more services and get more information provided by the Clouds. In this paper, we propose residential gateway architecture based on Cloud Computing. The residential gateway interconnects the household appliances and the Clouds. Our architecture is divided into four layers: physical layer, virtual devices layer, devices management layer and access Clouds layer. It is useful that the normal users can get benefit from the Clouds and it makes the Clouds extend the normal households. The architecture that we propose in this paper is a conceptual model and more work need to be done to implement it.